Corespondența Panait Istrati – Romain Rolland avatarurile unui „discurs îndrăgostit” - Bianca Burța-Cernat (Revista de Istorie și Teorie Literară)
This paper aims to analyze two different discourses included in the correspondence between Panait Istrati and Romain Rolland. First of all, Panait Istrati’s discourse – a strongly passionate “lover’s discourse” (according to Roland Barthes’s theory) – that tries to captivate the great French writer thanks to the energy of his creative personality. Secondly, Rolland’s discourse: reasonable and severe. This asymmetric relationship has an important cultural meaning that the present paper tries to underline following the rapports between the disciple and the master and also between Occident and Orient.